Lateral luxation of the elbow and its treatment in a kitten - Polat, E (Journal of the Hellenic Veterinary Medical Society, 2025)
Elbow luxations are one of the rare orthopedic problems in kittens. The primary goal in the treatment of elbow luxations is to minimize the limitation of movements of the cubiti joint. For this reason, although many techniques are used, different treatment options are still needed.In this report, it was aimed to share the lateral luxation of the elbow and its treatment in a three-month-old cat. It is very important that the applied operation technique does not restrict the normal movements of the elbow joint and that it is an alternative to routine operation techniques. In the operation, after the radius bone was fixed to the ulna bone with an orthopedic pin, the luxation at the elbow was fixed using a cerclage wire. The patient, who started using its foot on the third day of the postoperative period, was followed up for four months. In the interviews with the patient's owner, it was learned that the patient's condition was quite good and he could use his foot comfortably